PENGARUH PENERAPAN MEDIA BINGO GAMES TERHADAP PEMBELAJARAN AL-QUR’AN HADITS DI KELAS IV MI DARUSSALAM SUMBERMULYO JOMBANG: Jurnal Ilmu Pendidikan - Ni'mah, Maidatur Rizqon; widiyati, Evita (Al Tadib : Jurnal Ilmu Pendidikan, 2020)
This article discusses the effect of the application of Bingo games media on learning Al-Qur'an Hadith, aims to determine 1) the application of bingo games media in learning Al-Qur'an Hadith, 2) the effect of the application of bingo games media on learning Al-Qur ' an Hadith. This study used a quantitative approach with a true experimental design, researchers used the Mann Whitney Test hypothesis test. The results show that: 1) the application of bingo games media is in accordance with what has been prepared in the Learning Implementation Plan (RPP), 2) there is an effect of the application of bingo games media on learning Al-Qur'an Hadith in class IV MI Darussalam Sumbermulyo Jombang with a sign value obtained 0.032. Keywords: Media Bingo Games, Learning Al-Qur'an Hadith